2015
DOI: 10.1016/j.jvs.2015.01.052
|View full text |Cite
|
Sign up to set email alerts
|

Balloon angioplasty for revision of failing lower extremity bypass grafts

Abstract: Primary balloon angioplasty of failing lower extremity bypass grafts, notwithstanding the higher restenosis rate and the need for reintervention, appears to be safe and is associated with acceptable early and medium-term patency rates. Grafts with multiple lesions and those revised ≤6 months of the index operation showed a significant association with the need for a second revision at the same site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Previous studies have shown that grafts which are more likely to require multiple procedures to maintain patency are those with early graft stenosis (occurring within 6 months of implantation of the graft), long lesions (>2 cm), and multiple lesions. 10,11,20 The present study also showed a significantly better FFR in the medium and long term (more than a year) in grafts which had their first angioplasty after 6 months of implantation and those used in claudicants, but did not show any significant difference in longer or multiple lesions. This could have an impact when deciding between endovascular and open surgical revisions of vein graft stenoses.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Previous studies have shown that grafts which are more likely to require multiple procedures to maintain patency are those with early graft stenosis (occurring within 6 months of implantation of the graft), long lesions (>2 cm), and multiple lesions. 10,11,20 The present study also showed a significantly better FFR in the medium and long term (more than a year) in grafts which had their first angioplasty after 6 months of implantation and those used in claudicants, but did not show any significant difference in longer or multiple lesions. This could have an impact when deciding between endovascular and open surgical revisions of vein graft stenoses.…”
Section: Discussionsupporting
confidence: 62%
“…As the present series consisted of grafts with mainly non-reversed and in situ configurations, it is possible that certain situations such as retained valves causing graft failure might not be applicable to series with reversed saphenous vein grafts. Primary patency rates, assisted primary patency rates and in some series, secondary patency rates reported by Linni et al, 15 Ali et al, 10 van Oostenbrugge et al, 9 San Norberto et al, 16 Mofidi et al, 17 and Carlson et al 18 are summarized in Table 4. Apart from the present study, Linni et al 15 were the only others to report long-term outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…12 Dalman et al rightfully state that vein grafts can develop intrinsic lesions several weeks postoperatively that would not be detected on completion angiography, however this point should not detract from the value of completion angiography and should instead further spur close postoperative follow-up in order to detect these lesions and treat them before they result in graft occlusion. 3,[13][14][15] As such, unless there are prohibitive perioperative clinical constraints, completion angiograms should be routinely performed for infrainguinal bypasses that utilize venous conduit.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of our results with the literature is difficult because studies on the management of failing grafts are heterogenous regarding bypass type (autologous vs prosthetic), technique of bypass revision (endovascular vs surgical), start of the follow-up period (moment of bypass implantation vs moment of first bypass PTA), and the technique of angioplasty (simple balloon vs cutting balloon vs drug-eluting balloon). [13][14][15][16][17][18][19][20][21][22][23] Only one study until now has investigated infrainguinal bypass PTA by drug-coated vs plain angioplasty. The BYpass PAClitaxel balloon Study (BYPACS) study, published in 2014, reported outcomes of 32 patients treated with paclitaxel-coated PTA for anastomotic lesions in native or synthetic infrainguinal bypasses.…”
Section: Discussionmentioning
confidence: 99%